2023
DOI: 10.1038/s41598-023-37035-x
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of Angolan cold-water coral reefs (SE Atlantic) based on stable isotope analyses

Abstract: Cold-water coral (CWC) reefs of the Angolan margin (SE Atlantic) are dominated by Desmophyllum pertusum and support a diverse community of associated fauna, despite hypoxic conditions. In this study, we use carbon and nitrogen stable isotope analyses (δ13C and δ15N) to decipher the trophic network of this relatively unknown CWC province. Although fresh phytodetritus is available to the reef, δ15N signatures indicate that CWCs (12.90 ± 1.00 ‰) sit two trophic levels above Suspended Particulate Organic Matter (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 154 publications
0
0
0
Order By: Relevance
“…Nonetheless, model predictions showed that all seamounts present suitable areas where VMEs are likely to occur, supporting the expected ecological relevance of the seamounts in the region. Indeed, available image data showed pristine and diverse CWC gardens on Cadamosto Seamount (Orejas et al., 2022; Vinha et al., 2022) and exceptional sponge and crinoid fields and scleractinian coral reefs on Nola Seamount (Hansteen et al., 2014). In addition, three of the seamounts considered in our study – Boavista, Cabo Verde and Nola – are currently included in designated ecologically and biologically significant areas (EBSAs) (UNEP/CBD/COP/DEC/XII/22, 2014), where significant fishing activity occurs (Martins et al., 2022; Roast et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, model predictions showed that all seamounts present suitable areas where VMEs are likely to occur, supporting the expected ecological relevance of the seamounts in the region. Indeed, available image data showed pristine and diverse CWC gardens on Cadamosto Seamount (Orejas et al., 2022; Vinha et al., 2022) and exceptional sponge and crinoid fields and scleractinian coral reefs on Nola Seamount (Hansteen et al., 2014). In addition, three of the seamounts considered in our study – Boavista, Cabo Verde and Nola – are currently included in designated ecologically and biologically significant areas (EBSAs) (UNEP/CBD/COP/DEC/XII/22, 2014), where significant fishing activity occurs (Martins et al., 2022; Roast et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…One decade later, in 2021, the multidisciplinary research expedition iMirabilis2 (Orejas et al., 2022), part of the Horizon 2020 project iAtlantic, on board the R/V Sarmiento de Gamboa (UTM‐CSIC), was the first expedition dedicated to exploring the deep‐sea benthic communities of SW Cabo Verde. The recorded video transects, conducted using an ROV, revealed pristine CWC communities at Cadamosto Seamount (SW of Brava Island), including over 60 CWC morphospecies (Vinha et al., 2022).…”
Section: Methodsmentioning
confidence: 99%